Answer:
83,400
Step-by-step explanation:
Just carry the decimal point over to the right 4 places.
Step-by-step explanation:
To find the slope you use the slope formula which is y2-y2/x2-x1
And to find the y intercept you use y=mx +b. Yous substitute the slope as m and you substitute a point from the line to find b. Which is the y intercept
(1) -(5y - 2)= -5y+2
(2) -5 (3n + 1)= -15n - 5
(3) too long to do
The equation
in standard form looks like
.
Given equation of sphere be
.
We are required to express the given equation in the standard form of the equation of sphere.
Equation is basically relationship between two or more variables that are expressed in equal to form. Equation of two variables look like ax+by=c. It may be linear equation,quadratic equation, cubic equation or many more depending on the powers of variables. The standard form of the equation of sphere looks like
.
The given equation is
.
We have to break 22 which is in right side into various parts according to the left side of the equation.
![x^{2} +y^{2} +z^{2} +2x-4y-6z=-1-4-9+36](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2By%5E%7B2%7D%20%2Bz%5E%7B2%7D%20%2B2x-4y-6z%3D-1-4-9%2B36)
![x^{2} +y^{2} +z^{2} +2x-4y-6z+1+4+9=36](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2By%5E%7B2%7D%20%2Bz%5E%7B2%7D%20%2B2x-4y-6z%2B1%2B4%2B9%3D36)
![x^{2} +1+2x+y^{2}+4-4y+z^{2} +9-6z=36](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B1%2B2x%2By%5E%7B2%7D%2B4-4y%2Bz%5E%7B2%7D%20%2B9-6z%3D36)
![x^{2} +(1)^{2} +2*1*x+y^{2} +(2)^{2} -2*2y+z^{2} +(3)^{2} -2*3z=36](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%281%29%5E%7B2%7D%20%2B2%2A1%2Ax%2By%5E%7B2%7D%20%2B%282%29%5E%7B2%7D%20-2%2A2y%2Bz%5E%7B2%7D%20%2B%283%29%5E%7B2%7D%20-2%2A3z%3D36)
![(x+1)^{2} +(y-2)^{2} +(z-3)^{2} =(6)^{2}](https://tex.z-dn.net/?f=%28x%2B1%29%5E%7B2%7D%20%2B%28y-2%29%5E%7B2%7D%20%2B%28z-3%29%5E%7B2%7D%20%3D%286%29%5E%7B2%7D)
Hence the equation
in standard form looks like
.
Learn more about equations at brainly.com/question/2972832
#SPJ4
Answer:
The answer to your questions are in bold
Step-by-step explanation:
a)
C = ![\left[\begin{array}{ccc}-6&6\\-2&4\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-6%266%5C%5C-2%264%5C%5C%5Cend%7Barray%7D%5Cright%5D)
= -24 + 12
= -12
b) -1 7 -4 -1 -1 - 4 7 - 1 - 5 6
-2 -6 -8 8 = -2 - 8 -6 + 8 -10 2
2 -3 2 -7 2 + 2 -3 - 7 4 -10
-1 10 -6 5 -1 - 6 10 + 5 -7 15